Teachers' Metaphors on a School Organization - Bengi Erim Eker (Istanbul Kültür University, 2015)
As part of the late interest in the symbolic-interpretive approach to organizations, metaphors have attracted the attention of organization scientists in terms of their potential value in organizational analysis. Consistent with this, the purpose of this study was to identify the perceptions and descriptions of teachers on present and desired organizational structure and processes in a school in Turkey by using metaphors. In examining the organizational structure and processes, metaphors were used as an analysis technique. The results indicate that there seems to be a widely shared dissatisfaction among the teachers about the school which is, from the teachers' point of view, largely structured on mechanistic assumptions ignoring the needs of the teachers. Metaphors are very powerful analysis tools in capturing the various domains of a single organization (structural, human resources, sysmbolic/cultural) in a single study.